Polyphenols distribution and reserve substances analysis in cocoa somatic embryogenesis (2016)
ABSTRACT: In order to understand the causes of lack of regeneration in cacao somatic embryos, two cacao varieties with different responses to regeneration potential were described based on their capacity to store different compounds. It is well known that seed reserves play a central role in the regenerative capability of somatic embryos; thus, we followed histochemical changes and reserve fluctuations of proteins, polysaccharides and polyphenols during somatic embryogenesis (SE) in the two cacao varieties. The study showed that, in somatic embryos of the regenerating variety, polyphenols were localized mainly in the periphery of the embryo (epidermal cells) and proteins were the main storage substance in the embryo expression medium, while the non-regenerating variety had a high presence of polysaccharides with random distribution of polyphenols at the end of the embryo induction step.